PREVALENCE OF BRONCHOPULMONARY DYSPLASIA: JUSTIFICATIONS AND THE VOLUME OF THE REGIONAL CENTRE FOR DIAGNOSIS AND TREATMENT - Shipko, A.F. (World of Medicine and Biology, 2016)
It was justified for the first time, developed and proposed for the application of graphical and polynomial (quantitative) regional model incidence of bronchopulmonary dysplasia (BPD), depending on the number of premature children that allows generic comparison (at the state level) analysis of the level of diagnosis of BPD. The coefficients of the incidence of BPD in premature group pf children with different levels of body weight (BW) by calculating the ratio between the absolute number of children with BPD and the total number of children in the groups stratified by level MT deficit. It has bee grounded for the first time, developed and proposed for use the enhanced (multi-criteria) algorithm for the quantitative determination of the volume of activity centers dyagnostiki and treatment of BPD considering the regional born of preterm children and their degree of MT deficit. Inverse verification of this algorithm was achieved and demonstrated its sufficient accuracy for the application by the health care organizers. New is substantiated by the results of research and developed a nomogram (graphical and tabular versions) for the operational planning of the expected absolute number of patients with BPD, depending on the regional number of prematurely born children, which can be used in the planning of new and optimization of work of existing diagnostic centers and treatment of BPD .
Keywords: social medicine; bronchopulmonary dysplasia; the incidence; the regional center; models; algorithms; and scheduling